Removal of singularities in the inverse dynamics of parallel robots - ÖZDEMİR, MUSTAFA (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
It is commonly claimed in the literature that if the dynamic equations are made consistent at a type II singular configuration, then a parallel robot can pass through this configuration while the actuator forces remain bounded. However, in contrast to the existing literature, the present paper proves that the consistency of the dynamic model is not sufficient alone within this context, and derives the additional necessary conditions for this purpose. It is then shown that under these new conditions, type II singularities of parallel manipulators can be removed to guarantee finite and continuous inverse dynamics solutions while fully utilizing the workspace. These are achieved through a novel analysis of type II singularities of parallel robots based on the limit concept. Another contribution of the paper is the proposal for definitions of natural and actual orders of type II singularities.
Keywords: Parallel robot; Inverse dynamics; Singularity; Removable singularity; MANIPULATORS; TRACKING; MODEL